Efficacy of Blood Flow-Restricted Low-Load Resistance Training For Quadriceps Strengthening in Men at Risk of Symptomatic Knee Osteoarthritis. (September 2015) - Segal, Neil; Davis, Maria D.; Mikesky, Alan E.
Background: Greater quadriceps strength has been associated with lower risk of symptomatic knee osteoarthritis (OA) in older adults. However, factors that confer elevated risk of knee OA (eg, sedentary lifestyle, obesity, and knee injury) also contribute to a reduced tolerance of resistance training programs at ≥60% 1-repetition maximum (1RM). Therefore, the current study assessed whether concurrent application of blood flow restriction (BFR) to low-load resistance training is an efficacious and tolerable means of improving quadriceps strength in men at risk of symptomatic knee OA. Methods: Men older than age 45, with a history of knee injury or elevated body mass index (BMI), were randomized to low-load resistance training (30% 1RM) either with or without concurrent BFR. Isotonic double-leg press strength and isokinetic knee extensor strength were assessed before and after 4 weeks of training 3 times/wk. Knee pain (Knee Osteoarthritis Outcome Score) was assessed for tolerance. Results: Of the 42 men (mean age 56.1 ± 7.7 years) who were randomized, 41 completed the program. There were no significant intergroup differences in age, BMI, knee pathology, or muscle strength at baseline. Although leg press 1RM improved in both control and BFR groups, there were no significant intergroup differences in primary or secondary measures of muscle strength. The BFR was not associated with worsening of knee pain, but there was a significant improvement in knee pain in the control group. Conclusions: In comparison with training without BFR, addition of BFR to 30% 1RM resistance training for 4 weeks did not confer significantly greater increases in leg press or quadriceps strength in older men with risk factors for symptomatic knee OA.